Evaluation of the effect of the introduction of a hypertension club on the management of hypertension at a community health centre in the Cape Town Metropole - Nevilene Slingers; Pierre J.T. de Villiers (South African Family Practice)
Background: Hypertension is a widespread problem of immense economic importance in sub-Saharan Africa because of its high prevalence in urban areas, its frequent under-diagnosis, and the severity of its complications. A systematic review of interventions used to improve the management of hypertension in primary care showed that effective delivery of hypertensive care requires a systematic approach in the community. The rationale for establishing a hypertension club at the Mitchell’s Plain Community Health Centre (MPCHC), Cape Town, South Africa is based on the findings of and recommendations made by a study done previously at MPCHC by the Chronic Diseases of Lifestyle Programme of the Medical Research Council. This study found that the blood pressure of hypertensive patients was not optimally controlled and both the drug and non-drug management of hypertension needed to be improved. The patients had asked for the introduction of a dedicated hypertension club.